What Drives the Top Management Team's Sentiment and Perception of Future Risk and Uncertainty? A Selling-Capability Based View - Rahman, Mahabubur; Shimul, Anwar Sadat; Sun, Wenbin (Taylor & Francis, 2024)
Purpose